Pengaruh Partisipasi Anggaran Terhadap Kinerja Manajerial Dengan Komitmen Organisasi Dan Motivasi Kerja Sebagai Variabel Moderasi - Maria Natalia; Richard Anthony; Yunita Christy; Setiana, Sinta (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
This research intention to determine the effect of budget participation on managerial performance with organizational commitment and work motivation as moderating variables. The sample of this study were employees at managerial level (top and bottom). Researchers distributed 100 questionnaires spread to several manufacturing companies. Of the 100 questionnaires, 56 questionnaires were collected and 45 questionnaires were processed. The data collected were processed using the Multiple Liner Regression Correlation Test and Moderated Regression Analysis (MRA). Before testing the hypothesis, the researcher tested the validity, reliability, and classical assumption. The results showed that budget participation has a positive effect on managerial performance, even so when budget participation has a positive effect on managerial performance when moderated by organizational commitment and work motivation